Serum Amyloid A Protein Concentration in Blood is Influenced by Genetic Differences in the Cheetah (Acinonyx jubatus) - Franklin, Ashley D (J Hered, 2016)
Systemic amyloid A (AA) amyloidosis is a major cause of morbidity and mortality among captive cheetahs. The self-aggregating AA protein responsible for this disease is a byproduct of serum amyloid A (SAA) protein degradation. Transcriptional induction of the SAA1 gene is dependent on both C/EBPβ and NF-κB cis-acting elements within the promoter region. In cheetahs, 2 alleles exist for a single guanine nucleotide deletion in the putative NF-κB binding site. In this study, a novel genotyping assay was developed to screen for the alleles. The results show that the SAA1A(−97delG) allele is associated with decreased SAA protein concentrations in the serum of captive cheetahs (n = 58), suggesting genetic differences at this locus may be affecting AA amyloidosis prevalence. However, there was no significant difference in the frequency of the SAA1A(−97delG) allele between individuals confirmed AA amyloidosis positive versus AA amyloidosis negative at the time of necropsy (n = 48). Thus, even though there is evidence that having more copies of the SAA1A(−97delG) allele results in a potentially protective decrease in serum concentrations of SAA protein in captive cheetahs, genotype is not associated with this disease within the North American population. These results suggest that other factors are playing a more significant role in the pathogenesis of AA amyloidosis among captive cheetahs.